2018
DOI: 10.1002/path.5053
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic definition of molecular subgroups of small round cell sarcomas

Abstract: Sarcoma represents a highly heterogeneous group of tumours. We report here the first unbiased and systematic search for gene fusions combined with unsupervised expression analysis of a series of 184 small round cell sarcomas. Fusion genes were detected in 59% of samples, with half of them being observed recurrently. We identified biologically homogeneous groups of tumours such as the CIC-fused (to DUX4, FOXO4 or NUTM1) and BCOR-rearranged (BCOR-CCNB3, BCOR-MAML3, ZC3H7B-BCOR, and BCOR internal duplication) tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
334
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 265 publications
(368 citation statements)
references
References 38 publications
26
334
2
6
Order By: Relevance
“…Very recently, YAP1 – KMT2A fusion transcript was detected in a single unclassifiable sarcoma case in a large molecular series, and our report confirms that this fusion is recurrent in sarcoma. That case (SARC002) affected the chest wall of a 35‐year‐old woman; however, its histomorphology, immunophenotype and clinical course were undescribed.…”
Section: Discussionsupporting
confidence: 85%
“…Very recently, YAP1 – KMT2A fusion transcript was detected in a single unclassifiable sarcoma case in a large molecular series, and our report confirms that this fusion is recurrent in sarcoma. That case (SARC002) affected the chest wall of a 35‐year‐old woman; however, its histomorphology, immunophenotype and clinical course were undescribed.…”
Section: Discussionsupporting
confidence: 85%
“…[5][6][7][8][9][10][11][12][13] As the relationship between these tumors and conventional NC is still unclear, the classification terminology used in the literature varies, including NUT-associated tumors, 5 malignant epithelioid neoplasia, 7 NUT carcinomas, 11 and sarcomas. [5][6][7][8][9][11][12][13] In this study, we report a primary bone with ZNF592-NUTM1 fusion. [5][6][7][8][9][11][12][13] In this study, we report a primary bone with ZNF592-NUTM1 fusion.…”
Section: Discussionmentioning
confidence: 99%
“…2 With high sensitivity (87%) and specificity (100%), NUT immunostain has been utilized as a diagnostic substitute for molecular testing. [5][6][7][8][9][10][11][12][13] These tumors exhibit a wider and more heterogeneous morphologic spectrum compared to typical NC. 4 Recently, NUTM1 gene rearrangements have been increasingly identified in other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…CIC is typically fused to DUX4 or FOXO4 . However, NUTM1 has also recently emerged as a recurrent CIC fusion partner . CIC is a transcriptional repressor that interacts with DNA via a high motility group (HMG) box in conjunction with a C‐terminal C1 domain .…”
Section: Other Nutm1‐associated Solid Tumorsmentioning
confidence: 99%
“…Based on the partial similarity to NCs, Schaefer and colleagues concluded that a case of CIC‐NUTM1 NRN was best considered as a NC rather than a Ewing family tumor . However, others have shown that CIC‐NUTM1 tumors have transcriptome profiles similar to CIC‐DUX4 and CIC‐FOXO4 Ewing family tumors and are distinct from BRD4/3‐NUTM1 NCs . Moreover, their methylome profiles and overall morphology has also been reported to be extremely similar to CIC‐DUX4 and CIC‐FOXO4 tumors .…”
Section: Other Nutm1‐associated Solid Tumorsmentioning
confidence: 99%